Propaganda bancária: uma análise textual e orientada - Lara, Margarete Maria Fernandes do Nascimento (2009)
This dissertation is in the research line of Text and Discourse in Oral and Written Modalities and it has as subject the discourse of bank advertising. The fundamental question which drives the analysis undertaken is: In what linguistic-discursive artifices do producers of such advertisements rely on to argumentatively influence the readers? We assume it is the ideological character of the propagandistic discourse. Thus, we established a general goal: to analyze the discourse of bank advertising; and a specific goal: to identify the social and linguistic-discursive dimensions of bank advertising. For this study, we sought help, especially in the work of Norman Fairclough (2001) which addresses the discourse as a social practice. Regarding the works made about the language of advertising and its features, we make comments on some authors: Antônio Sandmann (1993), Adilson Citelli (1994 and 1990) and Luiz Carlos Assis Iasbeck (2002). Concerning the argument, we present the considerations of Chaim Perelman (1987) and Olivier Reboul (1998). The obtained results show us that the discourse of bank advertising is produced, textually, with several features such as cohesion, politeness, ethos, transitivity, theme, modality and the vocabulary that involves the meaning and the sense of the words. But, we also have the extralinguistic elements such as culture and ideology. We consider that the extralinguistic elements appear in the discourse, especially in interdiscursivity, in the intertextuality and in the assumption of the discourse of bank advertising. So, these are the linguistic-discursive artifices that the producers of bank advertising rely on to argumentatively influence the readers. And, it confirms our assumption that it is, above all, the ideological character of the propagandistic discourse that influences the readers and supposed consumers